2020
DOI: 10.1103/physrevresearch.2.033473
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous magnetic anisotropy and magnetic nanostructure in pure Fe induced by high-pressure torsion straining

Abstract: The formation of nanosized spin misalignment can be observed in pure Fe processed via high-pressure torsion (HPT) straining. The magnetic field dependence of the small-angle neutron-scattering profiles indicates that spin misalignment is conserved in magnetic fields up to 10 T. This result demonstrates that HPT straining provides anomalous magnetic anisotropy in pure Fe due to the high densities of the grain boundaries and lattice defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
(86 reference statements)
3
9
0
Order By: Relevance
“…We reemphasize that ℒ can be regarded as an estimate of the average defect size and 𝐻 * models the influence of the magnetostatic and magnetic anisotropy field contributions to the internal magnetic field. The estimated 'defect size' ℒ ~ 11 nm suggests that the origin of the spin misalignment observed in HPT Ni results from a high density of crystal defects on a scale smaller than the grain size, as previously suggested in HPT Fe 16 . In the remanent state, we estimate the penetration depth 𝛿 = 𝑙 c (𝐻 0 = 0) − ℒ of the spin disorder into the ferromagnetic Ni-phase to be ~ 22 nm (figure 3).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…We reemphasize that ℒ can be regarded as an estimate of the average defect size and 𝐻 * models the influence of the magnetostatic and magnetic anisotropy field contributions to the internal magnetic field. The estimated 'defect size' ℒ ~ 11 nm suggests that the origin of the spin misalignment observed in HPT Ni results from a high density of crystal defects on a scale smaller than the grain size, as previously suggested in HPT Fe 16 . In the remanent state, we estimate the penetration depth 𝛿 = 𝑙 c (𝐻 0 = 0) − ℒ of the spin disorder into the ferromagnetic Ni-phase to be ~ 22 nm (figure 3).…”
Section: Resultssupporting
confidence: 70%
“…14,15 for reviews of the magnetic SANS fundamentals and applications). This technique was recently used to demonstrate that in HPT Fe defects act as a source of an anomalous effective magnetic anisotropy field 16 . Here, we go a step further in the neutron data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we employ magnetic-field-dependent unpolarized small-angle neutron scattering (SANS) to clarify the role played by the defects in HPT-Ni. SANS is a powerful technique to characterize, on the mesoscopic length scale (1-500 nm), the crystalline as well as the magnetic microstructure of bulk magnetic materials [19][20][21][22][23][24][25][26]. In a very recent unpolarized SANS study on HPT-Ni [26], we have analyzed the field dependence of real-space magnetic correlations and found that the characteristic sizes of the spin disorder vary on a scale between about 10-30 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic SANS is a unique and powerful technique to investigate the magnetism of materials on the mesoscopic length scale of $1-300 nm [e.g. nanorod arrays (Grigoryeva et al, 2007;Gu ¨nther et al, 2014;Maurer et al, 2014), nanoparticles (Bender et al, 2019(Bender et al, , 2020Bersweiler et al, 2019;Za ´kutna ´et al, 2020;Kons et al, 2020;Ko ¨hler et al, 2021), INVAR alloy (Stewart et al, 2019) or nanocrystalline materials (Ito et al, 2007;Mettus & Michels, 2015;Titov et al, 2019;Oba et al, 2020;Bersweiler et al, 2021)]. For a summary of the fundamentals and the most recent applications of the magnetic SANS technique, we refer the reader to the literature (Mu ¨hlbauer et al, 2019;Michels, 2021).…”
Section: Introductionmentioning
confidence: 99%